2012
DOI: 10.1364/oe.20.007646
|View full text |Cite
|
Sign up to set email alerts
|

Comparative intrinsic optical signal imaging of wild-type and mutant mouse retinas

Abstract: Functional measurement is important for retinal study and disease diagnosis. Transient intrinsic optical signal (IOS) response, tightly correlated with functional stimulation, has been previously detected in normal retinas. In this paper, comparative IOS imaging of wild-type (WT) and rod-degenerated mutant mouse retinas is reported. Both 2-month and 1-year-old mice were measured. In 2-month-old mutant mice, time course and peak value of the stimulus-evoked IOS were significantly delayed (relative to stimulus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…3 indicate that the transient phototropic changes can partially contribute to IOS recording, which has the potential to be developed into a superior noninvasive method for spatiotemporal mapping of retinal function. 8,10 The different time courses of the IOSs at Zone 1 (periphery) and Zone 2 (center) suggest that the phototropic change of rod photoreceptors primarily contributes to the periphery IOS response. Multiple IOS origins, including neurotransmitter secretion, 32 refractive index change of neural tissues, 33 interactions between photoexcited rhodopsin and guanosine triphosphate (GTP)-binding protein, 34 disc shape change, 35 cell swelling, 36 etc., have been proposed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3 indicate that the transient phototropic changes can partially contribute to IOS recording, which has the potential to be developed into a superior noninvasive method for spatiotemporal mapping of retinal function. 8,10 The different time courses of the IOSs at Zone 1 (periphery) and Zone 2 (center) suggest that the phototropic change of rod photoreceptors primarily contributes to the periphery IOS response. Multiple IOS origins, including neurotransmitter secretion, 32 refractive index change of neural tissues, 33 interactions between photoexcited rhodopsin and guanosine triphosphate (GTP)-binding protein, 34 disc shape change, 35 cell swelling, 36 etc., have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…10 A fast digital camera (Neo sCMOS, Andor Technology, Belfast, UK) with pixel size 6 × 6 μm 2 was used for retinal imaging. A 20× water immersion objective with 0.5 NA was used for frog experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…13,28 In vitro IOS imaging of normal and mutant mouse retinas has been conducted to demonstrate disease-produced IOS distortions. 30 Laser-injured frog eyes have been used to demonstrate in vivo IOS mapping of localized retinal dysfunction. 27 Both in vitro and in vivo studies have shown that fast IOSs have different polarities and mainly originate from the photoreceptor outer segments in frog retinas.…”
Section: Introductionmentioning
confidence: 99%